2016
DOI: 10.3171/2016.1.spine14291
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of carbon fiber–reinforced polyetheretherketone cages for use as anterior struts following corpectomy

Abstract: OBJECTIVE Fibular allograft remains a widely used strut for corpectomy surgeries. The amount of graft material that can be packed into an allograft strut has not been quantified. Cages are an alternative to fibular allograft for fusion surgeries. The authors of this study assessed the suitability of carbon fiber–reinforced polyetheretherketone (CFRP) cages for anterior corpectomy surgeries. They further explored the parameters known to affect fusion rates in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…As mentioned, the modulus of elasticity of pure PEEK is 3.7-4.0 GPa [27,28], being lower than that of human cortical bone ranging from 7 to 30 GPa [9]. Therefore, many efforts have been spent by the researchers in enhancing the stiffness and strength of PEEK by reinforcing with HA microparticles, HA whiskers and carbon fibers for load-bearing orthopedic applications [39][40][41][42][43][44][45][46][47][131][132][133][134][135][136][137][138]. The elastic modulus of HA is 120.6 GPa [26], so it can be used as a reinforcement to stiffen PEEK.…”
Section: Peek/ha Microcompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, the modulus of elasticity of pure PEEK is 3.7-4.0 GPa [27,28], being lower than that of human cortical bone ranging from 7 to 30 GPa [9]. Therefore, many efforts have been spent by the researchers in enhancing the stiffness and strength of PEEK by reinforcing with HA microparticles, HA whiskers and carbon fibers for load-bearing orthopedic applications [39][40][41][42][43][44][45][46][47][131][132][133][134][135][136][137][138]. The elastic modulus of HA is 120.6 GPa [26], so it can be used as a reinforcement to stiffen PEEK.…”
Section: Peek/ha Microcompositesmentioning
confidence: 99%
“…PEEK-carbon fiber (CF) composites have been explored for orthopedic applications in posterior lumbar interbody fusion implants, screws, intramedullary nails, acetabular cups and dental implants [43][44][45][46][47][136][137][138][139][140][141][142][143]. Pure PEEK is inadequate for those applications because of insufficient stiffness.…”
Section: Peek/carbon Fiber Microcompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be proven that some natural fibers prevent stress shielding and increase bone remodeling [16, 17]. Furthermore, many studies have shown that flax fibers have better mechanical properties, similar to glass fibers, and lower water absorption, in comparison with other natural fibers [18–20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have shown that flax fibers have better mechanical properties, similar to glass fibers, and lower water absorption, in comparison with other natural fibers [18–20]. Recently, a hybrid natural fiber polymer composite material based on epoxy resin, enriched with sisal, jute and hemp fibers, was proposed for clinical application as orthopedic implants for femur bone prosthesis because of its good material properties, such as low density, increased tensile, compression, bending strength, and the mechanical behavior comparable to that of long human bones [17, 21]. In recent years, a new generation of transgenic plants was increasingly developed for the production of recombinant medicines and industrial products, such as vaccines, antibodies, biofuels and plastics [2225].…”
Section: Introductionmentioning
confidence: 99%